2003
DOI: 10.1053/eupc.2002.0299
|View full text |Cite
|
Sign up to set email alerts
|

Stability of far field R wave signals in different conditions

Abstract: given the lower FFRS thresholds with bipolar sensing, bipolar sensing is superior in avoiding FFRS compared with unipolar sensing. No differences were found in terms of amplitude thresholds and timing characteristics with patients supine, standing and at peak exercise. Thus, measurements made in the supine position are basically sufficient to predict the presence/absence of FFRS under different conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…However, Cools et al found that supine measurements were generally sufficient to predict the presence vs. absence of FFRW sensing at rest or at peak exercise. 10 Third, the prevalence and characteristics of FFRW were studied 7 days after pacemaker implantation and we did not examine the long-term evolution of the amplitude of sensed FFRW. However, in the study by Fung et al, the amplitude of FFRW at 90 days and at 1 year of follow-up was similar.…”
Section: Clinical Implications and Study Limitationsmentioning
confidence: 99%
“…However, Cools et al found that supine measurements were generally sufficient to predict the presence vs. absence of FFRW sensing at rest or at peak exercise. 10 Third, the prevalence and characteristics of FFRW were studied 7 days after pacemaker implantation and we did not examine the long-term evolution of the amplitude of sensed FFRW. However, in the study by Fung et al, the amplitude of FFRW at 90 days and at 1 year of follow-up was similar.…”
Section: Clinical Implications and Study Limitationsmentioning
confidence: 99%
“…13 Three features of the far-field signal should be considered, whether it is oversensed: relative amplitude, timing, and variability.…”
Section: Swerdlow Et Al Troubleshooting Icd Sensing II 213mentioning
confidence: 99%
“…Our study supports previous findings that a bipolar configuration is superior in rejecting ventricular far fields depending on the programmed sensitivity. 1,3,10,14 …”
Section: Unipolar Versus Bipolar Measurementsmentioning
confidence: 99%
“…A single pacemaker device type was chosen to exclude the influence of different sense amplifiers and filters on the study result. Measurements were performed 7 ± 3 months (range [3][4][5][6][7][8][9][10][11][12][13][14] after implantation of the device and pacing leads. Patient age was 66 ± 10 years, 79% of patients were male.…”
Section: Patient Characteristics and Pacing Systemsmentioning
confidence: 99%
See 1 more Smart Citation